Evaluation the Efficiency of Magnesium Oxide Nanoparticles in the Reduction of Ochratoxin A and in the Inhibition of Asperillusniger - Shahbaa H Majeed (Journal of Global Pharma Technology, 2020)
This study was conducted in Mycotoxins Laboratory /Department of Plant Protection/College of Agriculture at